The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.33394/jo-elt.v1i1.2401
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of PQRST and Sq3r Strategies Based on the Text Types Upon the Eighth Grade Students’ Reading Competency at SMPN 4 Singaraja

Abstract: This research aimed at investigating whether or not there is a different effect between PQRST and SQ3R strategies based on the text types upon the eighth grade students’ reading competency. This research was an experimental research with 2 X 2 factorial designs. The population was 6 classes (179 students) of grade VIII in SMPN 4 Singaraja in the academic year 2012/2013, in which 4 classes were sample of this research which was assigned into two groups, two classes with 60 students were PQRST strategy group, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Secondly, Sandiarsa et al (2013) found that there was different effect between PQRST and SQ3R strategies on students' reading competency and there was no interactional effect between both methods and text types. It almost similar to the result of this study although this study has different compared method, that was Small Group Discussion.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Secondly, Sandiarsa et al (2013) found that there was different effect between PQRST and SQ3R strategies on students' reading competency and there was no interactional effect between both methods and text types. It almost similar to the result of this study although this study has different compared method, that was Small Group Discussion.…”
Section: Discussionmentioning
confidence: 88%
“…The result showed that PQRST method and CTL approach improve students' learning outcome on chemistry subject about periodic table. On the contrary, Sandiarsa et al (2013) in his comparative research of PQRST (Preview, Question, Read, State, and Test) and SQ3R Strategies based on the text types upon the eighth grade students' reading competency at SMPN 4 Bali, showed that there was different effect between PQRST and SQ3R Strategies on students' reading competency and there is no interactional effect between both methods and text types (narrative and recount on students' reading competency.…”
Section: Introductionmentioning
confidence: 98%